Seleksi Mikrob Filoplan dan Endofit sebagai Agens Hayati Penyakit Gugur Daun Karet (Corynespora cassiicola) - Khaerati Khaerati; Yulius Ferry; Rusli Rusli (Pusat Penelitian dan Pengembangan Perkebunan, 2018)
Leaf fall disease in rubber caused by Corynespora cassiicola fungi significantly decreases rubber productivity. C. cassiicola causes leaves to fall all year round, a delay in the tapping of immature rubber plants, yield decrease of producing plants, and even death of susceptible clones. The study aimed to obtain phylloplane and endophytic microbes potentially to inhibit the disease, was conducted from January to December 2016. The study used randomized complete design to assess antagonistic fungi and phylloplane and endophytic bacterias toward C. cassiicola in isolates obtained through exploration in West Java and West Kalimantan. Pathogen isolation showed Corynespora sp with pale brown color, single conidia which slightly bended, shaped like a stick that is swollen at the base, with 2–14 septa. Inhibitory analysis found 42 fungi isolates and 19 bacteria isolates potentially inhibiting C. cassiicola. Six fungi isolates have an inhibitory ability of ≥90%, consisting of two phylloplane fungi isolates (DTJF11 and CPSR7) and four endophytic fungi (CEBPM15, CEBPM23, CEBPM27, and CEPR9) with lysis, mycoparasitism, competition, and antibiosis inhibitory mechanism. The identification showed fungi isolate of DTJF11 is classified as Trichoderma asperellum, CPSR7 as Talaromyces pinophilus, and CEBPM15 as Amanita tenuifolia. Potential bacterial isolates as biological agents are BP7, L3, BP3, BP4, BP5 and BP6 isolates, which have inhibitory power of 28.54%–40.94%, with antibiosis inhibition mechanism.